Translational opportunities of single-cell biology in atherosclerosis - De Winther, Menno P. J.; Bäck, Magnus; Evans, Paul; Gomez, Delphine; Goncalves, Isabel; Jørgensen, Helle F; Koenen, Rory R; Lutgens, Esther; Norata, Giuseppe Danilo; Osto, Elena; Dib, Lea; Simons, Michael; et al. (European heart journal, 2023)
The advent of single-cell biology opens a new chapter for understanding human biological processes and for diagnosing, monitoring, and treating disease. This revolution now reaches the field of cardiovascular disease (CVD). New technologies to interrogate CVD samples at single-cell resolution are allowing the identification of novel cell communities that are important in shaping disease development and direct towards new therapeutic strategies. These approaches have begun to revolutionize atherosclerosis pathology and redraw our understanding of disease development. This review discusses the state-of-the-art of single-cell analysis of atherosclerotic plaques, with a particular focus on human lesions, and presents the current resolution of cellular subpopulations and their heterogeneity and plasticity in relation to clinically relevant features. Opportunities and pitfalls of current technologies as well as the clinical impact of single-cell technologies in CVD patient care are highlighted, advocating for multidisciplinary and international collaborative efforts to join the cellular dots of CVD.
Online veröffentlicht: 07. Dezember 2022
Gesehen am 18.06.2024